Manajemen Pemasaran Pendidikan Madrasah Ibtidaiyah Qita Kota Malang Sebagai Lembaga Pendidikan Baru - Zahrotun Bariroh (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2022)
Recently, marketing management in the world of education is very much needed in line with the competition between educational institutions that is getting stronger because it is driven from various aspects, both the needs of society to the increasingly unlimited digital world. Marketing Management is needed for all educational institutions, both new and old institutions in building and maintaining their positive and attractive image. This research aims to understand and describe what are the objectives of marketing in the education zone, especially in Madrasah Ibtidaiyah QITA, then what are the elements of the marketing mix strategy that affect the marketing in MI QITA and the marketing management process itself. In this study, researchers used qualitative research methods with a case study approach, as well as data collection techniques based on the results of in-depth interviews, observations and documentation of facts in the field. The results of this study are the form of details of the expected objectives of MI QITA's marketing management as a new institution, elements of the marketing mix that affect marketing and marketing management consisting of planning, organizing, implementing and documentation.